2013
DOI: 10.1007/s00127-013-0788-6
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient care 50 years after the process of deinstitutionalisation

Abstract: PurposeThroughout the past 50 years mental health services have aimed to provide and improve high quality inpatient care. It is not clear whether there has been improvement as service users and nursing staff have both expressed frustration at the lack of therapeutic activities. In particular, it may be that the changing levels of symptoms over the past 50 years may affect engagement with ward activities.MethodsEight wards in a health care trust in London serving an inner city and urban populations participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…Engagement in inpatient activity has also been found to be associated with perceived quality of inpatient care (Csipke et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Engagement in inpatient activity has also been found to be associated with perceived quality of inpatient care (Csipke et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…) and few organized care activities (Csipke et al . ; Radcliffe & Smith ). Comparable studies from the past five decades have indicated that inpatient milieus are becoming increasing less engaging over time (Csipke et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low staffing levels, administrative demands and restrictive measures to maintain safety (Csipke et al., ; Thomson & Hamilton, ) are cited as barriers to therapeutic engagement. With bed numbers declining, only the most acutely unwell people are admitted to inpatient units (Royal College of Psychiatrists, ).…”
Section: Introductionmentioning
confidence: 99%